2017
DOI: 10.1017/s1463423617000214
|View full text |Cite
|
Sign up to set email alerts
|

Cohort differences in exercise adherence among primary care patients referred for mental health versus physical health conditions

Abstract: Aim: To compare the characteristics of mental health and physical health participants attending an exercise referral scheme (ERS) and investigate associations with their adherence to exercise. Background: While people referred to an ERS with a mental health diagnosis have similar initial rates of uptake as physical health participants, they are more likely to drop out. Comparisons of the groups to understand their differences and how these might impact on their adherence have been limited by the typically low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…Depressed patients instead, may have a more challenging clinical profile given that they have suffered tenacious symptoms, including psychosocial impairment that led to a mental health service, and they may often experience failure or disappointment because the service use uncovers the disease severity/complexity and the need for systematic care (Bursztajn & Barsky, ; Maguire, Cullen, O'Sullivan, & O'Grady‐Walshe, ; Morgan, ). To this extent, depressed patients referred to exercise on referral schemes are, unsurprisingly, showing high dropout rates, often the highest among all health referrals (Crone et al., ; James et al., ; Tobi et al., ). Therefore, our findings that stem from trials with patients with a referral or clinical diagnosis of depression are representative to routine practice and, thus, of additional value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressed patients instead, may have a more challenging clinical profile given that they have suffered tenacious symptoms, including psychosocial impairment that led to a mental health service, and they may often experience failure or disappointment because the service use uncovers the disease severity/complexity and the need for systematic care (Bursztajn & Barsky, ; Maguire, Cullen, O'Sullivan, & O'Grady‐Walshe, ; Morgan, ). To this extent, depressed patients referred to exercise on referral schemes are, unsurprisingly, showing high dropout rates, often the highest among all health referrals (Crone et al., ; James et al., ; Tobi et al., ). Therefore, our findings that stem from trials with patients with a referral or clinical diagnosis of depression are representative to routine practice and, thus, of additional value.…”
Section: Discussionmentioning
confidence: 99%
“…Media respondents may have strong outcome expectations or motivation to lifestyle changes; Blumenthal and Ong () reported that community volunteers of exercise trials for depression are typically motivated to exercise. Instead, depressed patients recruited through health services do not seem to be comparably motivated, as they show high dropout rates from exercise on referral schemes (Crone, Johnston, Gidlow, Henley, & James, ; James et al., ; Tobi, Kemp, & Schmidt, ). In addition, a number of trials reviewed by these three meta‐analyses included samples with other mood disorders (e.g., dysthymia), or samples with older adult (+65 years) or both adult (18–65 years) and older adult depressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Acceptability. People with mental health issues may be at a particular risk for dropping out in physical activity programs (e.g., Cooney et al, 2013;Tobi, Kemp, & Schmidt, 2017). This issue must be addressed within the field.…”
Section: Structured Call For Future Researchmentioning
confidence: 99%
“…Across these studies, there are some consistent predictors of outcomes. For example, increased uptake is associated with being female or older [7][8][9][10], and adherence with being male or older [6,7], or on a physical rather than a mental health referral pathway [11]. Limited work has suggested that there may be differences in uptake and adherence based on the health condition and/or disability status [9,12,13], with higher rates for musculoskeletal and cardiovascular than other forms of referrals.…”
Section: Inequalities In Uptake Adherence and Outcomesmentioning
confidence: 99%